Pengaruh Pemberian Motivasi Dalam Bentuk Honorarium Terhadap Peningkatan Kinerja Karyawan Pada Dinas Sosial Kota Prabumulih - Rikkie Dekas (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2018)
Tujuan penelitian -. This study aims to identify and analyze motivation in the form of an honorarium to the improving employee performance at Dinas Sosial Kota Prabumulih.Desain penelitian – The variables used in this study is given motivation and improving employee performance.The analytic technique used in this research is validity test, descriptive analysis, reliabilitas test, and regression analysisTemuan – The effect of giving motivation in the salary form with the  increasing of  employement work at prabumulih city social service is the magnitude of the influence of 57.6%, while the remaining 42.4% is influenced by other factors. This states that motivation in the form of salary has a positive and significant effect on the performance of employees in the pre-city social service department. This means that the better the motivation of work that is owned by employees will provide good performanceKeterbatasan penelitian -.Value –.Keywords: given motivation and improving employee performance